Property of Tensor Satisfying Binary Law 4 - koji (European Journal of Applied Sciences, 2022)
I have already reported "Property of Tensor Satisfying Binary Law 3". This article improved a proof part in article "Property of Tensor Satisfying Binary Law 3". The Proposition that improvement was carried out is Proposition4-8, Proposition10-15 in article "Property of Tensor Satisfying Binary Law 3". The Proposition of article "Property of Tensor Satisfying Binary Law 3" will become stronger by this improvement.